Angiolymphoid hyperplasia with eosinophilia versus Kimura's disease: a case report and a clinical and histopathological comparison - Julien Totti de Bastos; Camila Roos Mariano da Rocha; Priscila Mara Chaves e Silva; Bruno Messias Pires de Freitas; Flávia de Freire Cassia; João Carlos Regazzi Avelleira (Sociedade Brasileira de Dermatologia, 2017)
Abstract Angiolymphoid hyperplasia with eosinophilia is a rare and benign vascular tumor whose etiology remains uncertain. It clinically presents itself by angiomatous papules or nodules located on the head and neck. Many controversies in the literature are found in relation to angiolymphoid hyperplasia with eosinophilia and Kimura's disease - its main differential diagnosis - due to their clinical and histopathological similarities. However, currently, most studies agree that they are distinct diseases. The present case illustrates a characteristic description of angiolymphoid hyperplasia with eosinophilia and also highlights the main differences with Kimura's disease.